A New Species of Leptolalax from Sarawak, Western Borneo (Anura: Megophryidae) - Ramlah, Zainudin; Matsui, Masafumi; Nishikawa, Kanto (Zoological Society of Japan, 2014)
A new megophryid species is described from southwestern Sarawak, Malaysian Borneo. In appearance, Leptolalax marmoratus sp. nov. is most similar to L. hamidi also from southwestern Sarawak, but differs from it by mtDNA sequence, larger body size, and higher dominant frequency of advertisement call. The assumption that more than one species of Leptolalax coexist at one locality in Borneo is supported. The finding of the new species raises the species number of Leptolalax known from Borneo to nine, and the island is thought to be one of the diversification centers of the genus.